Analisis Identitas Genetik Ikan Gabus Sentani (Oxyeleotris heterodon) berdasarkan Marka Gen Sitokrom Oksidase 1 - Dailami, Muhammad; Maulana, Antajala Rian; Siahaan, Marthin Daniel Theo Gratia; Kusuma, Wahyu Endra; Agamawan, Lalu Panji Imam; Toha, Abdul Hamid A.; Yuniarti, Ating (Journal of Tropical Diversity, 2025)
The Sentani snakehead fish (Oxyeleotris heterodon) is an endemic fish species that inhabits Lake Sentani and several other lakes in Papua Province, Indonesia. This species has important ecological and economic value, but is vulnerable to environmental change and overexploitation. Genetic identification, especially using the Cytochrome Oxidase 1 (COI) gene, is very important for conservation efforts and understanding the genetic diversity of Sentani Snakehead Fish. DNA barcoding techniques with the COI gene have become the standard method in molecular identification of species, allowing rapid and accurate identification. Unfortunately, the Sentani Snakehead Fish faces various threats such as habitat degradation, pollution, overfishing and the introduction of invasive foreign species. Therefore, genetic research is becoming increasingly important to support conservation efforts, providing in-depth understanding of the population status and adaptive potential of species. The results of DNA amplification and sequencing of COI gene fragments showed a DNA sequence with a length of 619 base pairs with the composition A (23.9%), G (18.1%), C (29.1%), T (28.9%). The results of identification by homology analysis in the NCBI and BOLD databases showed the highest similarity at 97.58% and 97.84% with the O. lineolate sequence. This is because there is no O. heterodon sequence from the COI gene fragment found in Genbank or the BOLD system. Phylogenetic tree analysis with several sequences that have close similarities shows a difference in clade between the O. heterodon sequence from this study with the O. lineolate sequence and other species.